MENINGKATKAN KEMAMPUAN MEMBUAT CECIMPEDAN MENGGUNAKAN MODEL PBL BERORIENTASI 4C (CREATIVITY, CRITICAL THINKING,COLLABORATION, AND COMMUNICATION) SISWA KELAS X PH 5 SMK NEGERI 5 DENPASAR TAHUN PELAJARAN 2023/2024 - Ni Komang Ayuni Damayanti; Nyoman Astawan; I Kadek Adhi Dwipayana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Based on data analysis in the initial reflection which still shows the learning outcomes of students who are still lacking, research was carried out by applying the 4C (Creativity, Critical Thinking, Collaboration, And Communication) oriented Problem Based Learning (PBL) model in learning Balinese, especially cecimpedan material. This study aims to determine the ability of students to write cecimpedan and determine student responses in class X PH 5 SMK Negeri 5 Denpasar in the 2023/2024 academic year with the research subjects being 40 students. This research uses theories including: (1) writing, (2) Balinese paribasa, (3) 21st century learning, (4) 4C in learning, (5) Problem Based Learning (PBL) model. Data were collected using test and observation methods, while the data processing method used descriptive statistics. The results of this study showed that before the application of the 4C-oriented Problem Based Learning (PBL) model (Creativity, Critical Thinking, Collaboration, And Communication) the average student score was 62.55. With clasical learning completeness only 22.5%. In cycle I, it increased to 82.65 with clasical learning completeness reaching 87.5%. Student responses to the application of the 4C-oriented Problem Based Learning (PBL) model (Creativity, Critical Thinking, Collaboration, And Communication) also increased from pre-cycle to cycle I. In the pre-cycle, the average student response was 58.77 with a category of less and increased in cycle I to 86.37% with a good category